(untitled) (Scientia Agricola, 2020)
Stylosanthes capitata Vogel and Stylosanthes macrocephala M.B.Ferreira & Sousa Costa are two forage leguminous species of agronomic importance for animal husbandry in tropical environments. The physical mixture of both species (80 % S. capitata and 20 % S. macrocephala) comprises the commercial cultivar “Estilosantes Campo Grande”. However, proximity of fields for seed production may contaminate seed lots, compromising seeds quality. The combined use of dominant and co-dominant molecular markers is an appropriate strategy to certificate genetic purity and perform diversity studies of cultivars. In this research, a set of ISSR (Inter-Simple Sequence Repeat polymorphic DNA) and SSR (Simple Sequence Repeat polymorphic DNA) molecular markers were standardized to characterize S. capitata and S. macrocephala species and evaluate the genetic purity of commercial samples. Four ISSR markers (UBC 2, 864, 885, 886) and SSR marker SC18-01 G4B showed precise species-specific electrophoretic fingerprints for both species. Electrophoretic patterns of ISSR molecular markers should be displayed first to confirm the sample identification. The structure analysis showed that the less contaminated sample was S. capitata with 97 % of its genetic composition assigned to a single genetic cluster vs. 95 % for S. macrocephala. S. capitata has greater genetic diversity (ISSRHe:0.292; SSRHe:0.57) than S. macrocephala (ISSRHe:0.285; SSRHe:0.16); however, this difference was only significant with SSR molecular markers. As these genetic resources have considerable ecological, agronomic and economic importance, tools for accurate species identification and genetic studies are essential for further seed multiplication, as well as for improvement and conservation of cultivars